The Effect of Product Innovation and Service Quality on Impulsive Purchases with Brand Equity as a Moderating Variable - Netty Laura; Ayu Ramandha (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of product innovation and service quality on impulse buying moderated by brand equity. The sample used in this study amounted to 153 respondents from prospective consumers and consumers of Ayam Mama in Jakarta which were obtained from distributing questionnaires using google forms. This research uses Smart PLS 03 software to test the hypothesis under study. The results showed that product innovation had an effect on impulse buying with significant T-Statistics and P Values. However, service quality has no effect on impulse buying with T-Statistics and P Values that are not significant and very low. This study also shows that brand equity has an effect on impulse buying with significant and highest T-Statistics and P Values of the 5 hypotheses tested. For the brand equity moderation hypothesis, it can strengthen the effect of product innovation on impulse buying, but brand equity moderation weakens the effect of service quality on impulse buying.